MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA “SERASIK” UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS III DI SDN 5 RAHTAWU - Fitri Wahyuningtiyas; Dwi Amelia Noor; Putri Nor Aini; Fitriyah Amaliyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The low level of elementary school students' mathematical conceptual understanding remains a major issue in mathematics learning, particularly in the topic of angles. This condition is caused by teacher-centered instruction, limited active student participation, and the lack of engaging instructional media. This study aimed to examine the effect of implementing the Problem-Based Learning (PBL) model assisted by the "SERASIK" learning media on the mathematical conceptual understanding of third-grade students at SDN 5 Rahtawu. The study employed a quantitative approach using a quasi-experimental research design with a One-Group Pretest–Posttest Design. The research participants consisted of 18 third-grade students, including 10 girls and 8 boys. Data were collected through tests, observations, and documentation. Data analysis was conducted using descriptive and inferential statistics, including the Shapiro–Wilk normality test, the Paired Samples t-test, and the N-Gain test. The results showed that the mean pretest score of 64.94 increased to 83.29 on the posttest, representing an improvement of 18.35 points. The Paired Samples t-test yielded a significance value of 0.000 (< 0.05), indicating that the implementation of the Problem-Based Learning (PBL) model assisted by the "SERASIK" learning media had a statistically significant effect on students' mathematical conceptual understanding. Furthermore, the N-Gain score of 0.6271 fell within the moderate category, indicating that the instructional intervention was moderately effective in improving students' mathematical conceptual understanding. Based on these findings, it is recommended that teachers implement the Problem-Based Learning (PBL) model supported by concrete learning media such as "SERASIK" in mathematics instruction and provide more varied learning activities to optimize all indicators of students' mathematical conceptual understanding.